Phytochemical Screening and Antimicrobial Activity of Combination of Piper betle and Moringa oleifera Extracts - Arifin, Siti Hakimah Aprilia Garini; Firdhausi, Nirmala Fitria; Hidayati, Irul; Faizah, Hanik (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
The inappropriate use of antibiotics can lead to pathogenic bacteria developing multiple drug resistance, making infectious disease treatment crucial. Thus, the discovery of novel antibiotics from natural materials, such as plant extracts or their combinations, is critically needed. Extracts of green betel (Piper betle) and Moringa (Moringa oleifera) leaves are known to have antimicrobial activity. This study aimed to determine the chemical content and antimicrobial activity of ethanol extracts of the combination of green betel leaves and Moringa leaves against Staphylococcus aureus, Escherichia coli, and Candida albicans. Green betel and Moringa leaves were macerated in 96% ethanol to extract secondary metabolites. Secondary metabolites were analyzed using phytochemical screening. Antimicrobial activity was tested using disk diffusion using various concentrations: EF1 (25% betel leaves + 75% moringa leaves), EF2 (50% betel leaves + 50% moringa leaves), and EF3 (75% betel leaves + 25% moringa leaves). Phytochemical tests showed that the ethanol extracts of betel leaves contained flavonoids, alkaloids, tannins, and saponins, and no terpenoids, while moringa leaves contain flavonoids, tannins, saponins, and terpenoids, but no alkaloids. S. aureus and E. coli had the highest inhibition zones at EF3 (75% betel leaves + 25% moringa leaves) concentrations, with average inhibition zones of 21.72 mm and 20.98 mm, respectively, and C. albicans at EF2 (50% betel leaves + 50% moringa leaves) concentration, with an average inhibition zone of 26.52 mm, with a very strong inhibition category.